Fraudulent, cloned and hijacked journals in Latin America - Alhuay-Quispe, Joel (2025)
The proliferation of predatory publishing affects both the dynamics of scientific communication and their mechanisms for promoting research. An emerging but under-studied issue involves fraudulent, hijacked and cloned website journals, as a fraud to appropriate expired web domains or clone webpage of legitimate journals —practices that are often not considered criminal acts in some Latin American countries. This study compiles and documents the first report about hijacked and cloned scholarly journals from Argentina, Brazil, Colombia, Chile, Costa Rica, Mexico, and Venezuela. Based on the findings, recommendations on ethical aspects related to scientific editing are proposed for management of Latin American publishing.